Uplink analysis with mobile devices using directional-smart antennas. (5th October 2005) - Gavish, Bezalel; Ofek, Yoram; Whitaker, Roger M.
Ne of the main challenges of today's networking is how to increase the capacity of wireless data networks. Given the inherent limitations of radio frequency (RF) transmission capacity, a promising approach is to divide the 2D/3D space into multiple subspaces and to apply spatial channel reuse, which has the potential: (1) to increase aggregate system capacity, (2) to increase the wireless transmission range, (3) to reduce signal-to-noise and signal-to-interference ratio (SNR/SIR), (4) to reduce fading and (5) to reduce power consumption. This paper focuses on how using switched-beam antenna, on mobile devices (stations), can improve wireless communications. Specifically, we study the potential benefit of using a selected one of a multiple flat panel directional antennas, where the antenna selection is performed dynamically – packet-by-packet. The initial results are promising and show significant improvements of various aspects of the wireless system performance.